Efisiensi Penurunan Kadar Natrium (Na+) Dan Klorida (Cl-) Pada Air Laut Menggunakan Tanah Lempung Dengan Metode Penukar Ion - Utami Khairunnisa; Shinta Elystia; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Research efficiency decreased levels of chloride ion in sea water by ion exchange method which utilitizes clay to do. The results of the initial analysis on the sea of chloride parameter indicates the concentration parameter exceeds the quality standards PERMENKES 416/MENKES/PER/IX/1990. The research uses an ion exchange column with a diameter of 2 inches and a height of 1,2 meters. Media used is sea water of Bengkalis and clay activated with KOH 2 M. Variation used is the flow rate and time of observation. The flow rate used are 140 ml/mnt, 160 ml/mnt, 180 ml/mnt and 200 ml/mnt and time of observation used are 1; 1,5; 2 hours. Concentration of chloride before research is 15.423 mg/L and after processing occurs at decreasing concentrations in each variation of chloride are 278 mg/L - 667 mg/L. This result shows that the ion exchange methode using activated clays are capable of removing of chloride concentration in sea water. Over all, the variation used in this research give effect to decreased of chloride in sea water. This is also evidenced in the removal efficiency of ion is 98,2 % - 95,7 %.Keyword : Flow rate and time of observation, Ion Exchange, Sea water, The activated clays.